Estado hídrico y demanda de fotosintesis de Quercus ilex, Quercus faginea y Pinus halepensis MICORRIZADOS ARTIFICIALMENTE CON Tuber melanosporum EN VIVERO - DOMÍNGUEZ, J. A.; R. PLANELLES; RODRÍGUEZ BARREAL, J. A.; SAÍZ DE OMEÑACA, J. A.; ZAZO, J.; TEYSSIERE, M.; MARTINEZ, G.; PINAZO, O. (III Congreso Forestal Español Congreso, 2001)
We have been carried out a periodic control in Quercus ilex, Quercus faginea and Pinus halepensis inoculated with Tuber melanosporum Vitt. during the first year of growth in nursery with a water-non stressed régime; in all the species, the minimum water potential and transpiration rate didn't reflect any differences for the treatment, but in some cases, the photosynthesis rate was major in inoculated seedlings. K.W.:
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: ectomycorrhiza; photosynthesis; Pinus halepensis; Quercus faginea; Quercus ilex; Tuber

Incidence des caractéristiques structurales du sous-sol sur l'entrée en production de Tuber melanosporum et d'autres champignons mycorhiziens - Callot, G.; Jaillard, B.; Braye, J. P.; Jalade, M. (Agronomie, 1996)
Effect of structural characteristics of subsoil on the fruiting of Tuber melanosporum and other mycorrhizal fungi. The collection sites for ascocarps of Tuber melanosporum Vitt were noted over four consecutive years in a truffle bed of live oaks (Quercus ilex) mycorrhized by T melanosporum. The mycorrhizas of Tuber and other fungi were checked 11 years after planting. At the same time, a detailed soil survey made it possible to distinguish different soil units within the truffle bed. Cartographic analysis of the data set showed that the mycorrhizal status and the location of the fungus collection sites were related to the structural characteristics of the subsoil. The presence of a slightly permeable clay subsoil discourages fruiting in both epigeal and hypogeal fungi. Soils presenting a shallow calcareous crust discourage the growth of hypogeal Tuber-type fungi, but encourage that of epigeal fungi. T melanosporum grows best in soils with a very porous horizon developed in contact with the calcareous bedrock. This horizon (termed Bbio by the authors) is characterized by an intensive biological activity.
Keywords: autoecology; fungi; limestone; Mycorrhizas; subsoil; Tuber